Histone Deacetylase Inhibitor Modulates NKG2D Receptor Expression and Memory Phenotype of Human Gamma/Delta T Cells Upon Interaction With Tumor Cells - Bhat, Jaydeep; Dubin, Samuel; Dananberg, Alexandra; Quabius, Elgar Susanne; Fritsch, Juergen; Dowds, C. Marie; Saxena, Ankit; Chitadze, Guranda; Lettau, Marcus; Kabelitz, Dieter (Frontiers in Immunology, 2019)
The functional plasticity and anti-tumor potential of human γδ T cells have been widely studied. However, the epigenetic regulation of γδ T-cell/tumor cell interactions has been poorly investigated. In the present study, we show that treatment with the histone deacetylase inhibitor Valproic acid (VPA) significantly enhanced the expression and release of the NKG2D ligands MICA, MICB and ULBP-2, but not ULBP-1 in the pancreatic carcinoma cell line Panc89 and the prostate carcinoma cell line PC-3. Under in vitro tumor co-culture conditions, the expression of full length and the truncated form of the NKG2D receptor in γδ T cells was significantly downregulated. Furthermore, using a newly established flow cytometry-based method to analyze histone acetylation (H3K9ac) in γδ T cells, we showed constitutive H3K9aclow and inducible H3K9achigh expression in Vδ2 T cells. The detailed analysis of H3K9aclow Vδ2 T cells revealed a statistically significant reversion of TEMRA to TEM phenotype during in vitro co-culture with pancreatic ductal adenocarcinoma cells. Our study uncovers novel mechanisms of how epigenetic modifiers modulate γδ T-cell differentiation during interaction with tumor cells. This information is important when considering combination therapy of VPA with the γδ T-cell-based immunotherapy for the treatment of certain types of cancer.